Prion-like propagation of Parkinson's disease - Brundin, Patrik (Henry Stewart Talks, 2014)
Parkinson's disease: symptoms and pathology (PD mutations and risk factors), Braak staging of Lewy body-related pathology in PD, The prion-like hypothesis, Key steps of alpha-synuclein pathology propagation (Release, Uptake, Seeding, Transport), In vivo and cell models from different species, Therapeutic targets: promoting degradation, antibody aided clearance, and preventing seeding of alpha-synuclein, Parkinson’s disease vaccine: first clinical studies